538. Percent Positivity of COVID-19 Testing in Children of Racial/Ethnic Minority Groups in Mississippi. (31st December 2020) - Inagaki, Kengo; Hobbs, Charlotte V
Abstract: Background: COVID-19 testing data in children from different backgrounds such as race/ethnicity can guide the strategies for controlling the pandemic. In this study, we aimed to characterize the percent positivity of real time reverse transcriptase polymerase chain reaction (RT-PCR) testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among children with different race/ethnicity in Mississippi, a state with historic racial health disparity. Methods: We performed a retrospective study using a deidentified COVID-19 registry abstracted from the electronic health record at the University of Mississippi Medical Center, the only academic institution in the state encompassing the main university hospitals and ambulatory sites statewide. Children aged 18 years or younger who underwent RT-PCR for SARS-CoV-2 between 11 March 2020 and 31 May 2020 were included in the study. The primary outcome of interest was positive SARS-CoV-2 RT-PCR test, and the primary exposure of interest was race/ethnicity. Multivariable analysis was performed by developing a logistic regression model. Results: Of 1838 children who underwent SARS-CoV-2 RT-PCR testing, 162 tested positive, corresponding to percent positivity of 8.8%. Non-Hispanic white children had percent positivity of 2.4%, which was substantially lower than that of non-white children (9.7%, 28.6%, and 11.5% for non-Hispanic black, Hispanic, and other race/ethnicity children, respectively) (Table). Older children (particularly those aged 10–18 years) also had higher percent positivity (Table, Figure). The risks associated with non-white race/ethnicity remained substantial after adjusting for insurance status, which was used as a surrogate for socioeconomic status (Figure). Table Figure Conclusion: We found a striking difference in percent positivity by race/ethnicity among children, suggesting inadequate allocation of testing resources to this population. Higher percent positivity among school age children may also have particular public health implications, considering their school attendance. We argue that minority children should not be left behind in data analysis, research, targeted testing and transmission reduction measures. Disclosures: All Authors : No reported disclosures